Obesity as a risk factor for dengue shock syndrome in children - Maria Mahdalena Tri Widiyati; Ida Safitri Laksanawati; Endy Paryanto Prawirohartono (Indonesian Pediatric Society, 2013)
Background Dengue hemorrhagic fever (DHF) leads to highmorbidity and mortality if not be treated properly and promptly.Obesity may play a role in the progression ofDHF to dengue shocksyndrome (DSS) and could be a prognostic factor.Objective To evaluate childhood obesity as a prognostic factorfor DSS.Methods We reviewed medical records of patients with DHFand DSS admitted to Department of Child Health, Dr. SardjitoHospital, Yogyakarta between June 2008 and February 2011.Subjects were aged less than 18 years and fulfilled WHO criteria(1997) for DHF or DSS. The exclusion criteria were the denguefever, a milder form of disease, or other viral infections. Riskfactors for DSS were analyzed by logistic regression analysis.Results Of342 patients who met the inclusion criteria, there were116 DSS patients (33 .9%) as the case group and 226 DHF patients(66.1%) as the control group. Univariate analysis revealed thatrisk factors for DSS were obesity (OR= 1.88; 95%CI 1.01 to3.5 l) ,secondary infection type (OR=0.82; 95%CI 0.41 to 1.63), plasmaleakage with hematocrit increase> 25% (OR=3.42; 95%CI 2.06to 5.65), platelet count < 20,000/Î¼L (OR= l.95; 95%CI 1.20 to3 .16), and inadequate fluid management from prior hospitalization(OR=9.ll; 95% CI 1.13 to 73.66). By multivariate analysis,plasma leakage with hematocrit increase > 25% was associatedwith DSS (OR=2.5 l; 95%CI 1.12 to 5.59), while obesity was notassociated with DSS (OR= l.03; 95%CI 0.32 to3.3 1).Conclusion Obesity is not a risk factor for DSS, while plasmaleakage with hematocrit increase > 25% is associated with DSS.